Gynecological Malignancies in Albania: The Challenges of Cancer Care in a Low Resource Country - Kleida Mati; Carmelo Pozzo; Elona Cekani; Kleva Qeraj; Jona Prifti; Olti Pecini; Arlinda Elmasllari; Fatilba Skoku; Cesare Romagnolo (Clinical and Experimental Obstetrics & Gynecology)
Objective: This literature review aims to provide a comprehensive assessment of the current state of gynecological cancers in Albania, including their epidemiology, screening, diagnosis, and treatment. It also aims to highlight the challenges that Albanian patients face in accessing appropriate treatment and to discuss the importance of data collection. This is the first comprehensive review of gynecological cancers in Albania. Mechanism: A comprehensive literature search was conducted using various databases to identify relevant studies and government reports. Government reports were used to supplement the data obtained from the International Agency for Research on Cancer and provide additional insights into the challenges and limitations of cancer data collection in Albania. Findings in Brief: Albania has a population of 1.18 million women aged 15 years and older who are at risk of developing gynecological cancers. The most prevalent gynecological cancers among Albanian women are endometrial, cervical, and ovarian cancers. Cervical cancer accounts for 30% of all gynecological cancers and is the main cause of cancer-related mortality in this group. Albanian women are at a lower risk of developing gynecological cancers than women in neighboring countries. The main risk factors for gynecological cancers in Albanian women include increasing age, obesity, and human papillomavirus (HPV) infection. However, no data are available on germline mutations associated with a hereditary risk of developing gynecological cancers. Recently, Albania has introduced a cervical cancer screening program along with HPV vaccination. Nonetheless, owing to lack of awareness and education about the disease and limited access to early screening programs, gynecological cancers are often detected at later stages. Treatment options for gynecological cancers in Albania remain largely unchanged and have not adapted to new molecular classification methods that could affect treatment decisions. Furthermore, new therapeutic options, such as immunotherapy and targeted agents, are not commonly used for gynecological cancers in Albania. Conclusions: Gynecological cancers remain a significant public health issue in Albania. Urgent action is needed to address the increasing burden of gynecological cancers, including investment in cancer control strategies, primary prevention, early detection, treatment, healthcare infrastructure, capacity building, and research to address specific national needs and implement evidence-based policies.